Strategi Pengembangan Ekowisata Mangrove Petengoran dengan Pendekatan Analisis ASOCA - Falia Azzahra Delawa; Dedy Yuliawan (Departement of Mathematics Education, 2024)
The Mangrove Petengoran ecotourism is a potential ecotourism site for development. However, based on the tourist visitation data in Gebang Village, Pesawaran Regency, the Mangrove Petengoran ecotourism still resulting in few visitors and remains at the level of an incipient tourism village according to the Ministry of Tourism and Creative Economy. The development of the Mangrove Petengoran ecotourism is expected to uphold the local community's economy. The purpose of this study is to determine the effective strategy for the development of the Mangrove Petengoran ecotourism village in Pesawaran Regency based on the ASOCA analysis perspective. Researchers identify the internal and external factors of the Mangrove Petengoran ecotourism. Following the acquisition of these factors, the result is integrated into the ASOCA matrix and subsequently assessed via the Litmus test to derive scores. These scores are then utilized to ascertain the strategic issues pertinent to the evolution of the tourist site. Based on the ASOCA analysis, eight highly strategic issues are identified as top priorities and primary concerns for decision-making or policy formulation based on their significant impact on future generations. Subsequently, there are five strategic issues that can be implemented, given the significant impact on the incoming community. Therefore, these prior issue can be utilized for the development of the Mangrove Petengoran ecotourism.